Relationships, Being-ness, and Voice: Exploring Multiple Dimensions of Humanizing Work with Black Girls. Issue 4 (1st October 2016) - Edwards, Erica; McArthur, Sherell A.; Russell-Owens, LaToya
ABSTRACT: This work argues for an approach to research and education practices that considers the historically deficit-based research practices and views on Black girls and develops humanizing research methods that consider the multiple oppressions that act as barriers for this group. Research must acknowledge the precarious position of Black girls in order to adequately address their needs and inform policy around Black girl achievement. We contend, along with Ruth Nicole Brown (2009 ), that the research process needs to celebrate Black girls as much as it works to relieve the social, political, and economic challenges they navigate. Through a series of vignettes, the authors explain how relationships, a regard for being, and voice offer methods for humanizing educational research with Black girls.